2020
DOI: 10.3389/fvets.2020.00096
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Endochin-Like Quinolones Against in vitro Cultured Besnoitia besnoiti Tachyzoites

Abstract: Endochin-like quinolones (ELQs) potently inhibit the proliferation of Plasmodium, Toxoplasma, Neospora, and Babesia by targeting the cytochrome b Qo and Qi sites and interfering with oxidative phosphorylation and pyrimidine biosynthesis. The activities of 14 different ELQs were assessed against B. besnoiti tachyzoites grown in human foreskin fibroblasts (HFF) by quantitative real time PCR. The values for 50% proliferation inhibition (IC50) of five ELQs were determined in a 3-days growth assay after an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Interestingly, our calculated values of IC 50 for ELQ-300 and ELQ-316 are in the same range or lower than values estimated for other related apicomplexans in previous studies. ELQ-316 IC 50 values of 7.97, 0.66 and 0.35 nM were established for Besnoitia besnoiti and Toxoplasma gondii tachyzoites, respectively [ 28 , 29 ]. In addition, a previous study demonstrated ELQ-300 IC 50 values of 15.4 and 23.1 nM for Plasmodium knowlsei and P. falciparum , respectively [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our calculated values of IC 50 for ELQ-300 and ELQ-316 are in the same range or lower than values estimated for other related apicomplexans in previous studies. ELQ-316 IC 50 values of 7.97, 0.66 and 0.35 nM were established for Besnoitia besnoiti and Toxoplasma gondii tachyzoites, respectively [ 28 , 29 ]. In addition, a previous study demonstrated ELQ-300 IC 50 values of 15.4 and 23.1 nM for Plasmodium knowlsei and P. falciparum , respectively [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specimens were polymerized at 65 • C overnight, ultrathin sections were cut on a Reichert and Jung ultramicrotome (Reichert and Jung, Vienna) and were placed on 300 mesh formvar-carbon coated nickel grids (Plano GmbH, Marburg, Germany). They were stained in Uranyless ™ and lead citrate (EMS, Hatfield, PA, USA) as described [30], and specimens were inspected on a CM12 TEM operating at 80 kV.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Interestingly, our calculated values of IC 50 for ELQ-300 and ELQ-316 are in the same range or lower than values estimated for other related apicomplexans in previous studies. ELQ-316 IC 50 values of 7.97, 0.66 and 0.35 nM were established for Besnoitia besnoiti and Toxoplasma gondii tachyzoites, respectively [28,29]. In addition, a previous study demonstrated ELQ-300 IC 50 values of 15.4 and 23.1 nM for P. knowlsei and P. falciparum, respectively [15].…”
Section: Resultsmentioning
confidence: 87%